PENERAPAN TEKNOLOGI INFORMASI UNTUK PEMERINTAH DAERAH - Iman Satoto, Kodrat (TEKNIK, 2008)
In developed countries like the United States and European countries, the application of informationtechnology in the areas of government have been significantly in creating a clean government andtransparent. Some examples include the implementation of the model B2B (business to business ecommerce)applications for the procurement of goods and services electronically (e-procurement), theshort message technology to accelerate the delivery of information and web-services to facilitate otherparties to get information although different technology and platform.Meanwhile, in our countries, the application of information technology in the field of governance is stillvery limited. This is because the source of funds and skilled human resources are very limited. Someexamples of the application of information technology that is already there; Portal made for each office,portals for profile local government and application for one stop services. Most of the local governmentbuild the system information partially so can occurred distortions such as inconsistencies of information.Apparently there has been no local government in Indonesia that utilize ICT (information andcommunication technology) extensively to achieve good governance.It is time for local governments to apply information technology, which currently is very mature to be ableto realize the government is clean and transparent. Starting with building a complete database (datacenter),followed by developing applications that require each local government office and eventually builtan executive information system that can generate strategic information needed to help make decisions.